Experimental Investigations of Sigma Vectors in Nodal Aberration Theory for Coma-Free Pivot Misalignment State of a Cassegrain Telescope - Meltem Yeşiltepe; Sefer Bora Lişesivdin (Gazi Üniversitesi Fen Bilimleri Dergisi)
The study aims experimental investigation of the sigma vectors in Nodal Aberration Theory for a customized non-aplanatic high-precision Cassegrain telescope under coma-free pivot point (CFPP) misalignment conditions. Rotating the telescope's secondary mirror at the CFPP introduces a specific misalignment condition, resulting in unchanged coma aberration across the field of view (FOV). Evaluating CFPP misalignment is essential for optical alignment processes. Investigating the field aberration vectors for the telescope’s CFPP misalignment state provides valuable insights into the behavior of field-dependent aberrations and enhances the understanding of CFPP misalignment conditions.